Assessing relapses and response to relapse treatment in patients with multiple sclerosis: a nursing perspective - Ross, Amy Perrin; Halper, June; Harris, Colleen J (International journal of MS care, 2012)
There are currently no assessment tools that focus on evaluating patients with multiple sclerosis (MS) who are experiencing a relapse or that evaluate patients' response to acute relapse treatment. In practice, assessments are often subjective, potentially resulting in overlooked symptoms, unaddressed patient concerns, unnoticed or underrecognized side effects of therapies (both disease modifying and symptomatic), and suboptimal therapeutic response. Systematic evaluation of specific symptoms and potential side effects can minimize the likelihood of overlooking important information. However, given the number of potential symptoms and adverse events that patients may experience, an exhaustive evaluation can be time-consuming. Clinicians are thus challenged to balance thoroughness with brevity. A need exists for a brief but comprehensive objective assessment tool that can be used in practice to 1) help clinicians assess patients when they present with symptoms of a relapse, and 2) evaluate outcomes of acute management. A working group of expert nurses convened to discuss recognition and management of relapses. In this article, we review data related to recognition and management of relapses, discuss practical challenges, and describe the development of an assessment questionnaire that evaluates relapse symptoms, the impact of symptoms on the patient, and the effectiveness and tolerability of acute treatment. The questionnaire is designed to be appropriate for use in MS specialty clinics, general neurology practices, or other practice settings and can be administered by nurses, physicians, other clinicians, or patients (self-evaluation). The relapse assessment questionnaire is currently being piloted in a number of practice settings.